Monozygous twins with hypothyroidism and diabetes mellitus. Issue 568 (February 1973) - Mitchell, I.; Lawson, A. A. H.
Abstract : Monozygous twins with diabetes mellitus and autoimmune hypothyroidism are described. The onset of the hypothyroidism was simultaneous, but one twin had had insulin-dependent diabetes mellitus for 9 years while the other twin developed insulin-independent diabetes concurrently with the hypothyroidism. Two other siblings had diabetes mellitus and one of them had a goitre, possibly lymphadenoid. The aetiology of autoimmune hypothyroidism is discussed, and evidence is presented which supports suggestions that diabetes mellitus may be an autoimmune disease.